DOI: 10.14264/uql.2016.975
|View full text |Cite
|
Sign up to set email alerts
|

Oral health in South East Queensland Koalas: Prevalence of periodontal disease and other pathologies

Abstract: The koala (Phascolarctos cinereus) is one of Australia's most highly specialised folivores with a diet exclusively of eucalyptus leaves to provide all nutritive needs. For this it is dependent on good dentition for optimal health and quality of life. The purpose of this study was to characterise and describe the level of oral health and disease in koalas and then create tools for ongoing analysis.The historical records over a 17-year period were noted for the koalas admitted to the Moggill Koala Hospital in So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
11
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 272 publications
(404 reference statements)
2
11
0
Order By: Relevance
“…FOHI were also mild to moderate with younger koalas having much lower index scores than older koalas. The pattern of poorer oral health observed in older koalas is similar to that seen in northern koalas and was similar to the rates recorded in other herbivores …”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…FOHI were also mild to moderate with younger koalas having much lower index scores than older koalas. The pattern of poorer oral health observed in older koalas is similar to that seen in northern koalas and was similar to the rates recorded in other herbivores …”
Section: Discussionsupporting
confidence: 81%
“…The results of our study showed that PD is a significant oral disease in South Australian koalas, with 84% of the koalas having some form of PD, 77% having gingivitis, and 65% presenting with periodontitis. The prevalence of PD detected in South Australian koalas was similar to free‐ranging koalas from Queensland, where the prevalence of PD was estimated to be 74% . However, Queensland koalas had lower levels of gingivitis and periodontitis, with a prevalence of 50% and 28%, respectively .…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations